Trade and Protection in the Asian Developing Region - Dean A. DeRosa (Asian Development Review, 1986)
Every period poses new challenges to the world economy. The last decade has been marked by a series of problems that have contributed to reduced growth rates or declines in global economic activity. These problems emerged from a sequence of related events, starting with oligopoly pricing of crude petroleum exports, followed by rapid world inflation, disinflation, and, most recently, high real interest rates and external debt repayment problems of an increasing number of developing countries. These economic developments have given rise to international concern about a new era of protectionism that could well have similar deleterious effects on the world economy as those that contributed to the Great Depression of the 1930s…